"Churcar" Alternatives to Development (Alternautas, 2014)
As ideas about development are so deeply rooted, attempts to seek alternatives are almost like swimming against the prevailing cultural current. To effectively pursue these alternatives, radical changes are necessary from the source. Instead of quoting Marx or Lenin, I consider more appropriate to draw inspiration from an old word of the Tacanas in Bolivia: “Churcar”.